Comparative production and reproduction performances of local and Murrah-cross buffaloes managed by smallholder farmers in Bhutan (SAARC Journal of Agriculture, 2015)
This study was undertaken to evaluate production and reproduction performances of local and Murrah-cross buffaloes managed by smallholder farmers of Bhutan. Data was collected from 80 buffalo farming households in three buffalo rearing districts (Samtse, Sarpang and Samdrupjongkhar) in the sub-tropical belts of Bhutan. There were 1- 2 milking buffaloes per household and the duration of the field study was from 14 -29 December, 2014. Results indicated that average herd size is six buffaloes per household and are managed through open grazing with supplementary feeding but without proper housing. Study also revealed that genetic up-gradation of local buffalo population through introduction of Murrah breeding bulls and heifers has improved their productivity. Average daily milk yield of Murrah-cross buffalo is 5.9±0.18 l/day/cow (Mean ±SE) which is significantly higher (p ?0.000) than that of local buffaloes yielding 2.6±0.04 l day-1. Murrah-cross buffaloes had better productive and reproductive efficiency than local buffaloes and have added advantage to buffalo farmers. Average age at first calving is 35.1±2.49 months (Mean±SD) for Murrahcross buffaloes compared to 43.4±6.86 months for local buffaloes. Similarly, lactation length for Murrah-cross buffaloes is 10.1±0.50 month which is longer than local buffaloes (9.2±1.90 month). Calving interval of 14.6±0.52 months for Murrah-cross is lower than that of local buffaloes (17.4±1.01). Sale of fresh milk, butter and cheese from these animals contributed a major share of household income (54%) and has helped to improve livelihoods of farmers despite major challenges faced: limited government support, shrinking of grazing areas and labour constraints. However, with intensified support, many farmers are enthusiastic to rear quality buffaloes that can be an opportunity to accelerate buffalo farming. Study concluded that owing to higher productivity of Murrah-cross buffaloes, it can be a viable dairy animal for subtropical belt of Bhutan. Regular exchange of breeding bulls, supply of quality heifers and artificial insemination facilities with adequate technical support are crucial for greater positive outcome of enhancing milk production in the country.SAARC J. Agri., 13(1): 200-206 (2015)